Negative plate, preparation method thereof and battery

By designing a multi-layer structure in the negative electrode sheet of a lithium-ion battery, including the negative current collector, the active layer and the functional layer, and using lithium titanate and surface density gradient in the functional layer, the problem of insufficient liquid absorption performance of the electrode sheet is solved, and the conductive performance and cycle life of the battery are improved.

CN120089687APending Publication Date: 2025-06-03JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510361304.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

The pole-plate liquid-absorbing performance of existing lithium-ion batteries is insufficient, resulting in a large internal resistance of the battery, affecting the circulation and rate performance.

Method used

A negative electrode sheet is designed, which consists of a negative electrode current collector, a first negative electrode active layer, a second negative electrode active layer and a first functional layer. The first functional layer contains lithium titanate, and the wetting property of the electrolyte is optimized by setting a surface density gradient of multiple regions.

Benefits of technology

By optimizing the electrode sheet structure, the wetting efficiency of the electrolyte is improved, the embedding and removal efficiency of lithium ions is improved, and the conductivity and cycle life of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120089687A_ABST
    Figure CN120089687A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative plate, a preparation method thereof and a battery. The negative plate comprises a first negative electrode active layer, a second negative electrode active layer and a first functional layer which are sequentially arranged from the current collector to the outside; the first functional layer of the negative plate comprises at least three regions which are sequentially arranged along a first direction, the surface density of each region is sequentially reduced along the first direction of the negative plate, and the difference value of the surface densities of any two adjacent regions is 20-80%; and the first direction of the negative plate is a direction from the tab side to a direction far away from the tab side in the width direction of the negative plate. The electrolyte is deposited at the bottom of the battery, lithium titanate with low coating amount is arranged on one side close to the electrolyte, and lithium titanate with high coating amount is arranged on the upper side far away from the electrolyte at the bottom, so that the electrolyte can rapidly and fully infiltrate the pole piece, the pole piece can be fully infiltrated by the electrolyte, and the service life of the battery is prolonged. And the lithium ion intercalation and deintercalation efficiency in the charging and discharging process is improved, so that the conductivity is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and particularly relates to a negative electrode sheet, a preparation method thereof, and a battery. Background Art

[0002] At present, lithium-ion batteries (LIBs ) are widely used in portable devices and electronic products. However, lithium-ion batteries still have some problems in the applications of electric vehicles and renewable energy storage power grids, including energy density, material cost, and use safety. In common aluminum-shell batteries, the electrolyte is located at the bottom of the battery, and the structure of the electrode sheet will directly affect the wetting effect of the electrolyte, thereby affecting the performance of the battery such as cycling and rate performance. In current product batteries, although the material design is carried out from the cross-section of the electrode sheet, the liquid absorption performance of the electrode sheet is still lacking, and the internal resistance of the battery is also slightly large.

[0003] Therefore, there is a need to develop a negative electrode sheet with good liquid absorption performance and excellent charge and discharge performance at present. Summary of the Invention

[0004] In view of this, the present invention is committed to providing a negative electrode sheet, a preparation method thereof, and a battery to improve the problems of the lack of liquid absorption performance of the electrode sheet and the large internal resistance of the battery in the prior art.

[0005] To solve the above technical problems, the present invention is implemented as follows:

[0006] In a first aspect of the present invention, a negative electrode sheet is provided. The negative electrode sheet includes a negative electrode current collector, a first negative electrode active layer provided on at least one side in the thickness direction of the negative electrode current collector, a second negative electrode active layer provided on the first negative electrode active layer and away from the negative electrode current collector, and a first functional layer provided on the second negative electrode active layer and away from the first negative electrode active layer. The first functional layer contains lithium titanate;

[0007] The first functional layer includes at least three regions arranged in sequence along a first direction, and the areal density of each region decreases in sequence along the first direction, and the difference in the areal density between any two adjacent regions is 20-80%; the first direction is the direction from the tab side to the side away from the tab side in the width direction of the negative electrode sheet.

[0008] Optionally, the first functional layer includes a first region, a second region, and a third region arranged in sequence along the first direction; optionally, the areal density of the first region is 0.008-0.0126 g / 1540.25 mm 2 . Optionally, the areal density of the second region is 0.0045-0.007 g / 1540.25 mm 2Optionally, the areal density of the third region is 0.0025 - 0.0039 g / 1540.25 mm 2 .

[0009] Optionally, the areal density of the first negative electrode active layer is 0.0715 - 0.0775 g / 1540.25 mm 2 , and the areal density of the second negative electrode active layer is 0.0725 - 0.0825 g / 1540.25 mm 2 .

[0010] Optionally, the porosity of the first negative electrode active layer is less than that of the second negative electrode active layer, and the difference between the porosity of the first negative electrode active layer and the porosity of the second negative electrode active layer is 10 - 20%.

[0011] Optionally, the porosity of the first negative electrode active layer is 20 - 25%; the porosity of the second negative electrode active layer is 25 - 40%.

[0012] Optionally, in the first functional layer, the porosity of the first region is 30 - 34%, the porosity of the second region is 36 - 41%, and the porosity of the third region is 42 - 50%.

[0013] Optionally, the ratio of the thickness of the first negative electrode active layer to the thickness of the second negative electrode active layer is 1:(1.2 - 1.5).

[0014] Optionally, the ratio of the thickness of the first negative electrode active layer to the thickness of the first functional layer is 1:(0.02 - 0.25); preferably, the thickness of the first negative electrode active layer is 40 - 100 μm; the thickness of the second negative electrode active layer is 48 - 150 μm; the thickness of the first functional layer is 2 - 10 μm.

[0015] Optionally, the first negative electrode active layer contains a first negative electrode material, and the second negative electrode active layer contains a second negative electrode material.

[0016] Optionally, the ratio of Dv50 of the first negative electrode material to Dv50 of the second negative electrode material is 1:(0.55 - 1.14).

[0017] Optionally, Dv50 of the first negative electrode material is 7.5 - 10 μm.

[0018] Optionally, Dv50 of the second negative electrode material is 5.5 - 8.5 μm.

[0019] Optionally, Dv50 of the lithium titanate is 0.4 - 3 μm.

[0020] Optionally, the first negative electrode material and the second negative electrode material are each independently selected from at least one of graphite, hard carbon, silicon oxide, and silicon carbon; preferably, the first negative electrode material is graphite and the second negative electrode material is graphite; more preferably, the first negative electrode material is primary particle graphite and the second negative electrode material is secondary particle graphite.

[0021] Optionally, the content of lithium titanate in the first functional layer is 92-96 wt%.

[0022] Optionally, in the first negative electrode active layer, the content of the first negative electrode material is 90-99 wt%.

[0023] Optionally, in the second negative electrode active layer, the content of the second negative electrode material is 80-98 wt%.

[0024] In the second aspect of the present invention, a battery is provided, and the battery includes the above-mentioned negative electrode sheet.

[0025] The present invention adopts the above technical solutions and has the following beneficial effects:

[0026] (1) In the negative electrode sheet of the present invention, from the current collector to the outside are the first negative electrode active layer, the second negative electrode active layer, and the first functional layer in sequence. Among them, the first functional layer contains lithium titanate, and lithium titanate can provide a stable lithium insertion / lithium extraction platform, improving the safety, fast charge and discharge ability, and cycle life of the battery.

[0027] Furthermore, the first functional layer includes at least three regions arranged in sequence along the first direction, and the areal density of each region decreases in sequence along the first direction, and the difference in areal density between any two adjacent regions is 20-80%; the first direction is the direction from the tab side to the side away from the tab side in the width direction of the electrode sheet. That is, in an aluminum shell battery, the electrolyte is deposited at the bottom of the battery. On the side close to the electrolyte, there is lithium titanate with a low coating amount, and on the upper side far from the bottom electrolyte, there is lithium titanate with a high coating amount, and its liquid absorption performance is stronger, enabling the electrolyte to infiltrate the electrode sheet more quickly and fully. In this way, the electrolyte can fully infiltrate the electrode sheet, improving the efficiency of lithium ion insertion and extraction during charge and discharge, and further improving the conductivity.

[0028] Other features and advantages of the present invention will be described in detail in the subsequent specific implementation section. Description of the Drawings

[0029] The drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific implementation, they are used to explain the present invention, but do not constitute a limitation to the present invention.

[0030] Figure 1 Shown is a schematic cross-sectional view of the negative electrode sheet in Example 1;

[0031] Figure 2 The figure shows a horizontal schematic diagram of the first functional layer in Embodiment 1.

[0032] Description of the reference numerals in the drawings

[0033] 0, negative current collector; 1, first negative active layer; 2, second negative active layer; 3, first functional layer;

[0034] 31, first region; 32, second region; 33, third region. Detailed implementation manners

[0035] The present invention discloses a negative electrode sheet, a preparation method thereof, and a battery. Those skilled in the art can draw on the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all regarded as included in the present invention. The methods and applications of the present invention have been described through preferred embodiments. It is obvious that relevant personnel can make changes or appropriate alterations and combinations to the methods and applications described herein without departing from the content, spirit, and scope of the present invention to implement and apply the technology of the present invention.

[0036] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0037] In the ranges disclosed herein, the endpoints and any values are not limited to the exact ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein. In this article, unless otherwise specified, data ranges include endpoints.

[0038] If there is no special description, all implementation manners and optional implementation manners of the present invention can be combined with each other to form new technical solutions.

[0039] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.

[0040] Unless otherwise specified, the terms "comprising" and "including" mentioned in the present invention mean open-ended, and can also be closed-ended. For example, the terms "comprising" and "including" can mean that other components not listed can also be included, or can only include the components listed.

[0041] In order to solve the problems of poor liquid absorption performance of the electrode and large internal resistance of the battery in the prior art, the present invention adopts the following technical solutions:

[0042] In a first aspect of the present invention, a negative electrode sheet is provided. The negative electrode sheet includes a negative electrode current collector, a first negative electrode active layer provided on at least one side in the thickness direction of the negative electrode current collector, a second negative electrode active layer provided on the first negative electrode active layer and away from the negative electrode current collector, and a first functional layer provided on the second negative electrode active layer and away from the first negative electrode active layer. The first functional layer contains lithium titanate.

[0043] The first functional layer includes at least three regions arranged in sequence in a first direction, and the areal density of each region decreases in sequence along the first direction, and the difference in areal density between any two adjacent regions is 20-80%; the first direction is the direction from the tab side to the side away from the tab side in the width direction of the negative electrode sheet.

[0044] The above-mentioned "the first negative electrode active layer is provided on at least one side surface of the current collector in the thickness direction" means that the first negative electrode active layer can be provided on one surface of the current collector in its own thickness direction, or can be provided on two surfaces of the current collector in its own thickness direction. Here, the "surface" can be the entire area of the current collector, or can be a partial area of the current collector. For example, in the embodiments of the present invention, this surface can be the entire area of the current collector. The present invention has no special limitation on this, as long as the purpose of the present invention can be achieved.

[0045] As an example, the current collector has two surfaces opposite to each other in its own thickness direction, and the first negative electrode active layer is provided on the two opposite surfaces of the current collector. Further, a second negative electrode active layer is formed on the surfaces of the first negative electrode active layers on both sides. Still further, a first functional layer is formed on the surfaces of the second negative electrode active layers on both sides. It can be understood that in other embodiments, the first negative electrode active layer can also be stacked on any one of the two surfaces of the current collector.

[0046] In the silicon-doped negative electrode sheet of the present invention, the material of the current collector is not specifically limited.

[0047] The negative electrode sheet of the present invention, from the current collector to the outside, successively includes a first negative electrode active layer, a second negative electrode active layer, and a first functional layer. Among them, the first functional layer contains lithium titanate, and lithium titanate can provide a stable lithium insertion / delithiation platform, improving the safety, fast charge-discharge ability, and cycle life of the battery.

[0048] Furthermore, the first functional layer includes at least three regions arranged successively in a first direction, and the areal density of each region decreases successively along the first direction, and the difference in areal density between any two adjacent regions is 20%-80%; the first direction is the direction from the tab side to the side away from the tab side in the width direction of the electrode sheet. That is, in an aluminum shell battery, the electrolyte deposits at the bottom of the battery. On the side close to the electrolyte, there is lithium titanate with a low coating amount, and on the upper side far from the bottom electrolyte, there is lithium titanate with a high coating amount, which has stronger liquid absorption performance, enabling the electrolyte to infiltrate the electrode sheet more quickly and fully. In this way, the electrolyte can fully infiltrate the electrode sheet, improving the efficiency of lithium ion insertion and extraction during charge and discharge, and further enhancing the conductivity.

[0049] In a preferred embodiment of the present invention, the first functional layer includes a first region, a second region, and a third region arranged successively in a first direction;

[0050] According to the present invention, the areal density of the first region can be 0.008-0.0126 g / 1540.25 mm 2 . Exemplarily, the areal density of the first region can be any value within the range of 0.008 g / 1540.25 mm 2 , 0.009 g / 1540.25 mm 2 , 0.01 g / 1540.25 mm 2 , 0.011 g / 1540.25 mm 2 , 0.0126 g / 1540.25 mm 2 or any value within the range formed by any two of the above values. In the present invention, if the areal density of the first region is lower than 0.008 g / 1540.25 mm 2 , it may result in insufficient force for the functional layer to absorb the electrolyte; if the areal density of the first region is higher than 0.0126 g / 1540.25 mm 2 , it may result in a higher required areal density for the subsequent second region and third region, causing a reduction in the ion conduction performance of the entire electrode sheet.

[0051] According to the present invention, the areal density of the second region can be 0.0045-0.007 g / 1540.25 mm 2 . Exemplarily, the areal density of the second region can be 0.0045 g / 1540.25 mm 2, 0.005 g / 1540.25 mm 2 , 0.006 g / 1540.25 mm 2 , 0.0065 g / 1540.25 mm 2 , 0.007 g / 1540.25 mm 2 Any value within any of the above values or any value within the range formed by any two of the above values. In the present invention, if the areal density of the second region is lower than 0.0045 g / 1540.25 mm 2 , it may result in too small a gradient with the first region and insufficient upward electrolyte force; if the areal density of the second region is higher than 0.007 g / 1540.25 mm 2 , it may result in too much electrolyte in the middle of the electrode sheet and too little electrolyte at the edge of the electrode sheet, and uneven distribution may cause lithium plating at the edge.

[0052] According to the present invention, the areal density of the third region can be 0.0025 - 0.0039 g / 1540.25 mm 2 . Exemplarily, the areal density of the third region can be 0.0025 g / 1540.25 mm 2 , 0.003 g / 1540.25 mm 2 , 0.0035 g / 1540.25 mm 2 , 0.0036 g / 1540.25 mm 2 , 0.0039 g / 1540.25 mm 2 Any value within any of the above values or any value within the range formed by any two of the above values. In the present invention, if the areal density of the third region is lower than 0.0025 g / 1540.25 mm 2 , it may result in insufficient upward electrolyte force; if the areal density of the third region is higher than 0.0039 g / 1540.25 mm 2 , it may result in too high an areal density and affect the overall kinetic performance of the electrode sheet.

[0053] According to the present invention, the areal density of the first negative active layer can be 0.0715 - 0.0775 g / 1540.25 mm 2 . Exemplarily, the areal density of the first negative active layer can be 0.0715 g / 1540.25 mm 2 , 0.0731 g / 1540.25 mm 2 , 0.0745 g / 1540.25 mm 2 , 0.0756 g / 1540.25 mm 2 , 0.0775 g / 1540.25 mm 2Any value within the range formed by any of the above values or any two of the above values. In the present invention, if the areal density of the first negative electrode active layer is lower than 0.0715 g / 1540.25 mm 2 when, it may cause a decrease in the overall compaction of the electrode sheet; if the areal density of the first negative electrode active layer is higher than 0.0775 g / 1540.25 mm 2 when, it may cause a decrease in kinetic performance.

[0054] According to the present invention, the areal density of the second negative electrode active layer can be 0.0725 - 0.0825 g / 1540.25 mm 2 . Exemplarily, the areal density of the first negative electrode active layer can be 0.0725 g / 1540.25 mm 2 , 0.0731 g / 1540.25 mm 2 , 0.0787 g / 1540.25 mm 2 , 0.0806 g / 1540.25 mm 2 , 0.0825 g / 1540.25 mm 2 Any value within the range formed by any of the above values or any two of the above values. In the present invention, if the areal density of the second negative electrode active layer is lower than 0.0725 g / 1540.25 mm 2 when, it may cause insufficient kinetic performance; if the areal density of the second negative electrode active layer is higher than 0.0825 g / 1540.25 mm 2 when, it may cause a decrease in the electrode sheet compaction ability.

[0055] According to the present invention, the porosity of the first negative electrode active layer is less than the porosity of the second negative electrode active layer and the difference between the porosity of the first negative electrode active layer and the porosity of the second negative electrode active layer is 10 - 20%. As an example, the difference between the porosity of the first negative electrode active layer and the porosity of the second negative electrode active layer can be any value among 10%, 12%, 14%, 16%, 18%, 20% or any value within the range formed by any two of the above values. Through the above settings, the electrolyte can infiltrate deeper into the negative electrode sheet faster. Among them, setting the difference between the porosity of the first negative electrode active layer and the porosity of the second negative electrode active layer to 10 - 20% can have the technical effect of enabling the electrolyte to fully infiltrate the electrode sheet and quickly transport ions / electrons.

[0056] According to the present invention, the porosity of the first negative electrode active layer is 20-25%. As an example, the porosity of the first negative electrode active layer can be any value among 20%, 21%, 22%, 23%, 24%, 25% or any value within the range value composed of any two of the above values. When the porosity of the first negative electrode active layer is limited within the above range, it can have the technical effects of absorbing and retaining liquid and transporting ions / electrons.

[0057] According to the present invention, the porosity of the second negative electrode active layer is 25-40%. As an example, the porosity of the second negative electrode active layer can be any value among 25%, 30%, 35%, 40% or any value within the range value composed of any two of the above values. When the porosity of the second negative electrode active layer is limited within the above range, it can have the technical effect of improving the wettability of the electrolyte to the bottom layer.

[0058] According to the present invention, in the first functional layer, the porosity of the first region is 30-34%, the porosity of the second region is 36-41%, and the porosity of the third region is 42-50%. By setting different regions in the first functional layer to different porosities, it can have the technical effect of the electrolyte infiltrating towards the tab direction.

[0059] According to the present invention, the ratio of the thickness of the first negative electrode active layer to the thickness of the second negative electrode active layer is 1:(1.2-1.5). As an example, the ratio of the thickness of the first negative electrode active layer to the thickness of the second negative electrode active layer can be 1:1.2, 1:1.3, 1:1.4, 1:1.5. If the ratio of the thickness of the first negative electrode active layer to the thickness of the second negative electrode active layer is lower than 1:1.2, it may lead to insufficient compaction ability of the electrode sheet; if the ratio of the thickness of the first negative electrode active layer to the thickness of the second negative electrode active layer is higher than 1:1.5, it may lead to a decrease in fast charging ability.

[0060] According to the present invention, the ratio of the thickness of the first negative electrode active layer to the thickness of the first functional layer is 1:(0.02-0.25). As an example, the ratio of the thickness of the first negative electrode active layer to the thickness of the first functional layer can be any value among 1:0.02, 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25 or any value within the range value composed of any two of the above values. If the ratio of the thickness of the first negative electrode active layer to the thickness of the first functional layer is lower than 1:0.02, it may lead to a decrease in the fast charging performance of the electrode sheet; if the ratio of the thickness of the first negative electrode active layer to the thickness of the first functional layer is higher than 1:0.25, it may lead to insufficient liquid absorption performance.

[0061] According to the present invention, the thickness of the first negative electrode active layer is 40 - 100 μm. As an example, the thickness of the first negative electrode active layer can be any value among 40 μm, 60 μm, 80 μm, 100 μm or any value within the range formed by any two of the above values. If the thickness of the first negative electrode active layer is less than 40 μm, it may lead to insufficient compaction ability of the electrode sheet; if the thickness of the first negative electrode active layer is greater than 100 μm, it may lead to a decline in charging performance.

[0062] According to the present invention, the thickness of the second negative electrode active layer is 48 - 150 μm. As an example, the thickness of the second negative electrode active layer can be any value among 48 μm, 60 μm, 90 μm, 100 μm, 120 μm, 140 μm, 150 μm or any value within the range formed by any two of the above values. If the thickness of the second negative electrode active layer is less than 48 μm, it may lead to a decline in charging ability; if the thickness of the second negative electrode active layer is greater than 150 μm, it may lead to insufficient compaction ability of the electrode sheet, a decrease in flexibility, a reduction in peel strength, and an increased risk of short circuit.

[0063] According to the present invention, the thickness of the first functional layer is 2 - 10 μm. As an example, the thickness of the first functional layer can be any value among 2 μm, 4 μm, 6 μm, 8 μm, 10 μm or any value within the range formed by any two of the above values.

[0064] According to the present invention, the first negative electrode active layer contains a first negative electrode material, and the second negative electrode active layer contains a second negative electrode material. According to the present invention, the ratio of Dv50 of the first negative electrode material to Dv50 of the second negative electrode material is 1:(0.55 - 1.14). As an example, the ratio of Dv50 of the first negative electrode material to Dv50 of the second negative electrode material can be any value among 1:0.55, 1:0.75, 1:0.95, 1:1.05, 1:1.14 or any value within the range formed by any two of the above values. If the ratio of Dv50 of the first negative electrode material to Dv50 of the second negative electrode material is less than 1:0.55, it may lead to a smaller porosity of the second negative electrode material than that of the first negative electrode material, and the porosity gradient is not obvious. Based on the above settings, combined with factors such as slurry dispersion and coating during the preparation process, the porosity shows a gradient effect.

[0065] According to the present invention, the Dv50 of the first negative electrode material is 7.5 - 10 μm. As an example, the Dv50 of the first negative electrode material can be any value among 7.5 μm, 8.5 μm, 9.5 μm, 10 μm or any value within the range formed by any two of the above values. If the Dv50 of the first negative electrode material is lower than 7.5 μm, it may lead to a decrease in compaction ability; if the Dv50 of the first negative electrode material is greater than 10 μm, it may lead to a decline in charging ability.

[0066] According to the present invention, the Dv50 of the second negative electrode material is 5.5 - 8.5 μm. As an example, the Dv50 of the second negative electrode material can be any value among 5.5 μm, 6.5 μm, 7.5 μm, 8.5 μm or any value within the range formed by any two of the above values. If the Dv50 of the second negative electrode material is lower than 5.5 μm, it may lead to an excessively low aggregate particle size, resulting in fine powder and a too large battery impedance; if the Dv50 of the second negative electrode material is greater than 8.5 μm, it may lead to insufficient kinetic performance.

[0067] According to the present invention, the Dv50 of the lithium titanate is 0.4 - 3 μm. As an example, the Dv50 of the lithium titanate can be any value among 0.4 μm, 1 μm, 2 μm, 3 μm or any value within the range formed by any two of the above values. If the Dv50 of the lithium titanate is greater than 3 μm, it may lead to a decrease in the porosity of the electrode sheet.

[0068] According to the present invention, the first negative electrode material and the second negative electrode material are each independently selected from at least one of graphite, hard carbon, silicon oxide, and silicon carbon; preferably, the first negative electrode material is graphite and the second negative electrode material is graphite; more preferably, the first negative electrode material is primary particle graphite and the second negative electrode material is secondary particle graphite.

[0069] According to the present invention, due to the difference in graphite type, the strength of primary particle graphite is better than that of secondary particle graphite; for secondary particle graphite, due to the addition of asphalt, its kinetic performance is better than that of primary particle graphite. Additionally, due to the coating layer of secondary particle graphite, its kinetic performance is better than that of primary particle graphite.

[0070] According to the present invention, the content of lithium titanate in the first functional layer is 92 - 96 wt%. As an example, the content of lithium titanate in the first functional layer can be any value among 92 wt%, 93 wt%, 94 wt%, 95 wt%, 96 wt% or any value within the range formed by any two of the above values. If the content of lithium titanate in the first functional layer is lower than 92 wt%, it may lead to an excessive amount of auxiliary materials such as binders, affecting the cycle life; if the content of lithium titanate in the first functional layer is greater than 96 wt%, it may lead to insufficient binding force of the electrode sheet.

[0071] According to the present invention, in the first negative electrode active layer, the content of the first negative electrode material is 90-99 wt%. As an example, in the first negative electrode active layer, the content of the first negative electrode material can be any value among 90 wt%, 92 wt%, 95 wt%, 96 wt%, 99 wt% or any value within the range formed by any two of the above values. If the content of the first negative electrode material in the first negative electrode active layer is less than 90 wt%, it may cause excessive amounts of auxiliary materials such as binders, affecting the cycle life; if the content of the first negative electrode material in the first negative electrode active layer is greater than 99 wt%, it may cause insufficient adhesion of the electrode sheet and separation from the current collector.

[0072] According to the present invention, in the second negative electrode active layer, the content of the second negative electrode material is 80-98 wt%. As an example, in the second negative electrode active layer, the content of the second negative electrode material can be any value among 80 wt%, 85 wt%, 90 wt%, 95 wt%, 98 wt% or any value within the range formed by any two of the above values. If the content of the second negative electrode material in the second negative electrode active layer is less than 80 wt%, it may cause excessive amounts of auxiliary materials such as binders, affecting the cycle life; if the content of the second negative electrode material in the second negative electrode active layer is greater than 98 wt%, it may cause insufficient adhesion of the electrode sheet and separation from the first negative electrode active layer.

[0073] According to the present invention, the first negative electrode active layer and the second negative electrode active layer each independently further include a conductive agent, a binder, and a thickening agent.

[0074] According to the present invention, the mass ratio of the first negative electrode material, the conductive agent, the binder, and the thickening agent in the first negative electrode active layer is (90-98.6):(0.8-6):(0.4-2.5):(0.2-1.5). As an example, the mass ratio of the first negative electrode material, the conductive agent, the binder, and the thickening agent in the first negative electrode active layer can be any ratio among 90:0.8:0.4:0.2, 92:1:0.8:0.5, 95:5:2:1, 98.6:6:2.5:1.5, or any ratio within the above range.

[0075] According to the present invention, the mass ratio of the second negative electrode material, the conductive agent, the binder, and the thickening agent in the second negative electrode active layer can be (90-98.6):(0.8-6):(0.4-2.5):(0.2-1.5). As an example, the mass ratio of the first negative electrode material, the conductive agent, the binder, and the thickening agent in the first negative electrode active layer can be any ratio among 90:0.8:0.4:0.2, 92:1:0.8:0.5, 95:5:2:1, 98.6:6:2.5:1.5, or any ratio within the above range.

[0076] According to the present invention, the conductive agent may include at least one of carbon black, acetylene black, carbon nanotubes, carbon nanofibers or graphene. As an example, the conductive agent may be carbon black, may be acetylene black, may be carbon nanotubes, or may be a mixture of carbon black and acetylene black.

[0077] According to the present invention, the binder may include at least one of acrylonitrile, polyacrylic acid, vinylidene fluoride, vinyl alcohol, methacryloyl, acrylic acid, lithium acrylate, acrylamide, amide, imide, acrylate, styrene-butadiene rubber, sodium alginate, chitosan, ethylene glycol, monomers of guar gum, polymers of guar gum or copolymers of guar gum. As an example, the binder may be acrylonitrile, may be polyacrylic acid, may be vinylidene fluoride, may be vinyl alcohol, or may be a mixture of vinyl alcohol and imide.

[0078] According to the present invention, the thickener may include at least one of sodium carboxymethyl cellulose, carboxymethyl cellulose or lithium carboxymethyl cellulose. As an example, the thickener may be sodium carboxymethyl cellulose, may be carboxymethyl cellulose.

[0079] According to the present invention, the first functional layer may further include a binder and a conductive agent.

[0080] According to the present invention, the mass ratio of lithium titanate, binder and conductive agent in the first functional layer may be (92 to 96):(1 to 3):(1 to 3). As an example, the mass ratio of lithium titanate, binder and conductive agent in the first functional layer may be any ratio among 92:1:1, 93:1.5:2, 94:2:2, 95:2:2.5, 96:3:3, or any ratio within the above range.

[0081] According to the present invention, the negative electrode current collector may include one of copper foil, porous copper foil, nickel foam / copper foil, galvanized copper foil, nickel-plated copper foil, carbon-coated copper foil, nickel foil, titanium foil and carbon-containing porous copper foil. Preferably, the negative electrode current collector is selected from copper foil.

[0082] In one embodiment of the present invention, the method for preparing the negative electrode sheet may include the following steps:

[0083] (1) Slurry preparation: After mixing the first negative electrode material, conductive agent, binder, thickener and the first solvent, a first negative electrode active slurry is obtained; after mixing the second negative electrode material, conductive agent, binder, thickener and the second solvent, a second negative electrode active slurry is obtained; after mixing lithium titanate, conductive agent, binder and the third solvent, a first functional slurry is obtained.

[0084] (2) Coating: Coating the first negative electrode active paste on the surface of the current collector for the first drying, coating the second negative electrode active paste on the surface of the first negative electrode active layer for the second drying, coating the first functional layer paste on the surface of the second negative electrode active layer for the third drying, and after pressing, obtaining a negative electrode sheet.

[0085] According to the present invention, the preparation of the above-mentioned pastes can be carried out simultaneously without a sequential order.

[0086] According to the present invention, in the preparation process of the above-mentioned pastes, the first solvent, the second solvent, and the third solvent can be independently selected from water and / or N-methylpyrrolidone. As an example, the first solvent, the second solvent, and the third solvent can all be N-methylpyrrolidone.

[0087] According to the present invention, the mass ratio of the total mass of the first negative electrode material, conductive agent, binder, and thickener in the first negative electrode active paste to the mass of the first solvent can be 1:(43 - 55). As an example, the mass ratio of the total mass of the first negative electrode material, conductive agent, binder, and thickener in the first negative electrode active paste to the mass of the first solvent can be 1:(47 - 52).

[0088] According to the present invention, the mass ratio of the total mass of the second negative electrode material, conductive agent, binder, and thickener in the second negative electrode active paste to the mass of the second solvent can be 1:(42 - 54). As an example, the mass ratio of the total mass of the second negative electrode material, conductive agent, binder, and thickener in the second negative electrode active paste to the mass of the second solvent can be 1:(46 - 51).

[0089] According to the present invention, the mass ratio of the total mass of lithium titanate, conductive agent, and binder in the first functional paste to the mass of the third solvent can be 1:(42 - 55). As an example, the mass ratio of the total mass of lithium titanate, conductive agent, and binder in the first functional paste to the mass of the third solvent can be 1:(46 - 52).

[0090] According to the present invention, the compaction density during pressing can be 1.5 - 1.7 g / cm 3 . As an example, the compaction density can be 1.6.

[0091] In the present invention, the conditions for the first drying can include: temperature of 50 - 80 °C and time of 1.5 - 3 min; the conditions for the second drying can include: temperature of 60 - 100 °C and time of 1.5 - 3 min; the conditions for the third drying can include: temperature of 70 - 100 °C and time of 1.5 - 3 min.

[0092] The second aspect of the present invention provides a battery, which includes the above-mentioned negative electrode sheet and / or a negative electrode sheet prepared by the above-mentioned method.

[0093] In an embodiment of the present invention, the battery structure includes but is not limited to button cells, soft-pack batteries, cylindrical batteries, and the like.

[0094] The present invention places no particular restrictions on the negative electrode sheet, positive electrode sheet, electrolyte, etc. in the battery. Those skilled in the art can select according to actual needs as long as the object of the present invention can be achieved.

[0095] According to the present invention, the positive electrode active material in the positive electrode sheet includes at least one of lithium cobaltate, lithium nickelate, lithium manganate, lithium nickel manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminate, lithium manganese phosphate, lithium iron manganese phosphate, or lithium iron phosphate. As an example, the positive electrode active material in the positive electrode sheet can be lithium cobaltate, can be lithium nickelate, can be lithium manganate, or can be lithium nickel manganate.

[0096] The present invention will be further described in detail below through examples. All raw materials used in the examples can be obtained through commercial channels.

[0097] Example 1

[0098] First negative electrode active slurry

[0099] Mix secondary particle graphitized product: conductive agent: binder: thickener in a mass percentage of 96.5%: 1.0%: 1.7%: 0.8%, add deionized water and stir, adjust the viscosity to obtain the first negative electrode active slurry; wherein, the Dv50 of the secondary particle graphitized product is 7.5um, the conductive agent is carbon black (SP), the binder is polyacrylic acid (PAA), and the thickener is sodium carboxymethyl cellulose (CMC); the total mass ratio of the secondary particle graphitized product, conductive agent, binder, and thickener in the first negative electrode active slurry to the mass of deionized water is 1:48.

[0100] Second negative electrode active slurry

[0101] Mix single particle carbonized product: conductive agent: binder: thickener in a mass percentage of 97.2%: 1.0%: 1.0%: 0.8%, add deionized water and stir, adjust the viscosity to obtain the second negative electrode active slurry; wherein, the Dv50 of the single particle graphitized product is 6.5um, the conductive agent is carbon black (SP), the binder is polyacrylic acid (PAA), and the thickener is sodium carboxymethyl cellulose (CMC); the total mass ratio of the secondary particle graphitized product, conductive agent, binder, and thickener in the second negative electrode active slurry to the mass of deionized water is 1:49.

[0102] First functional slurry

[0103] Mix lithium carbonate, conductive agent, and binder in a mass ratio of 95%, 2.5%, and 2.5%, respectively, and stir with N-methylpyrrolidone to obtain the first functional slurry. Among them, the Dv50 of lithium carbonate is 0.8 μm, the conductive agent is carbon black (SP), the binder is polyacrylic acid (PAA), and the thickener is sodium carboxymethyl cellulose (CMC). The mass ratio of the total mass of lithium carbonate, conductive agent, and binder in the first functional slurry to the mass of N-methylpyrrolidone is 1:49.

[0104] Coat

[0105] Coat the first negative electrode active slurry on both sides of the copper foil along the thickness direction, and after drying, coat the second negative electrode active slurry on the surface of the first negative electrode active layer and then dry. Subsequently, use the spraying method to make the first functional slurry adhere to the second material active layer, and the air flow is high and the density is high near the side of the tab, and gradually decreases from top to bottom to present a gradient structure. Perform drying, rolling (compaction density is 1.6 g / cm 3 ), and slitting to obtain the negative electrode sheet of the secondary battery. The cross-sectional schematic diagram of the negative electrode sheet in this embodiment is as shown in Figure 1 shown, and the transverse schematic diagram of the first functional layer is as shown in Figure 2 shown.

[0106] The thickness of the first negative electrode active layer is 62 μm, the areal density is 0.715 g / 1540.25 mm 2 , and the porosity is 22%; the thickness of the second negative electrode active layer is 80 μm, the areal density is 0.715 g / 1540.25 mm 2 , and the porosity is 27%; the first functional layer is equally divided into a first region, a second region, and a third region from the tab downwards; among them, the thickness of the first region is 4 μm, the areal density is 0.01 g / 1540.25 mm 2 , and the porosity is 33%; the thickness of the second region is 3 μm, the areal density is 0.0055 g / 1540.25 mm 2 , and the porosity is 37%; the thickness of the third region is 2 μm, the areal density is 0.003 g / 1540.25 mm 2 , and the porosity is 45%.

[0107] Example 2

[0108] The difference between Example 2 and Example 1 is that in Example 2, the Dv50 of the secondary particle graphitized product is 8 μm, the Dv50 of the single particle graphitized product is 7 μm, the thickness of the first negative electrode active layer is 65 μm, and the porosity is 23%; the thickness of the second negative electrode active layer is 82 μm, and the porosity is 27.5%;

[0109] The rest are the same as in Example 1.

[0110] Example 3

[0111] Example 3 is different from Example 1 in that the Dv50 of the single-particle graphitized product is 7.5 μm, the thickness of the first negative electrode active layer is 65 μm, and the porosity is 23%; the thickness of the second negative electrode active layer is 82 μm, and the porosity is 27%.

[0112] The rest are the same as those in Example 1.

[0113] Example 4

[0114] Example 4 is different from Example 1 in that the Dv50 of lithium titanate is 2 μm, and the rest are the same as those in Example 1.

[0115] Example 5

[0116] Example 5 is different from Example 1 in that the thickness of the first region in the first functional layer is 4.5 μm, the areal density is 0.012 g / 1540.25 mm 2 , the porosity is 31%; the thickness of the second region is 3 μm, the areal density is 0.0055 g / 1540.25 mm 2 , the porosity is 37%; the thickness of the third region is 1.5 μm, the areal density is 0.0027 g / 1540.25 mm 2 , and the porosity is 43%.

[0117] Comparative Example 1

[0118] Comparative Example 1 is different from Example 1 in that the negative electrode sheet of Comparative Example 1 does not contain the first functional layer.

[0119] Comparative Example 2

[0120] Comparative Example 2 is different from Example 1 in that Comparative Example 2 only contains the first negative electrode active layer, and the thickness of the first negative electrode active layer is 160 μm, and the porosity is 23.4%; it does not contain the second negative electrode active layer and the first functional layer in Example 1;

[0121] The rest are the same as those in Example 1.

[0122] Comparative Example 3

[0123] Comparative Example 3 is different from Example 1 in that the slurry of the first functional layer in Comparative Example 3 is uniformly sprayed, that is, the first functional layer of Comparative Example 3 is a uniform region;

[0124] The rest are the same as those in Example 1.

[0125] Performance Test

[0126] 1. Battery Preparation

[0127] Preparation of the positive electrode sheet: Lithium iron phosphate, binder, and dispersant were dispersed in N-methylpyrrolidone in a ratio of 97.88%:2%:0.12% to control the slurry viscosity at 6000 mPas and the solid content at 68%. It was evenly coated on carbon-coated aluminum foil, dried, rolled, and slit to obtain the positive electrode sheet.

[0128] Separator: A polyethylene (PE) separator with a thickness of 12 μm was selected as the separator.

[0129] Electrolyte: In a glove box filled with inert gas, dimethyl carbonate and ethylene carbonate were mixed in a mass ratio of 1:1 to obtain an organic solvent. Then, the lithium salt LiPF 6 was dissolved in the organic solvent with a lithium salt concentration of 1 mol / L to obtain the electrolyte. Assembly of the battery: The negative electrode sheet, separator, and positive electrode sheet were wound to obtain an electrode core, which was then placed in a battery case, dried, filled with electrolyte, encapsulated, formed, and sorted to obtain the lithium-ion battery.

[0130] 2. Testing

[0131] (1) Peel strength test: The negative electrode sheet was fixed in the fixture of a universal tensile testing machine so that the peeling direction was perpendicular or opposite to the sample surface. Then, the sample was loaded at a certain speed until peeling occurred. Based on the data of force and displacement recorded by the universal tensile testing machine during the loading process, the peel strength between the coating and the base film was calculated.

[0132] (2) Resistance test: A battery internal resistance tester was used to connect the positive and negative electrodes of the battery to measure the battery internal resistance data.

[0133] (3) Capacity retention rate test: At room temperature of 25 °C, with the initial and cut-off voltages of 2.5 V and 3.65 V, it was charged at 3C to 3.65 V, and then charged at a constant voltage of 3.65 V until the current decreased to 0.05C. It was discharged at 0.5C to 2.5 V, then charged at 3C to 3.65 V again, and charged at a constant voltage of 3.65 V until the current decreased to 0.05C. It was discharged at 0.5C to 2.5 V. The battery was cycled for charge and discharge in this way, and the capacity retention rates at the 100th, 300th, and 500th cycles were calculated.

[0134] (4) Lithium plating test: At room temperature of 25 °C, with the initial and cut-off voltages of 2.5 V and 3.65 V, charge at 3C to 3.65 V, then charge at a constant voltage of 3.65 V until the current decreases to 0.05C, discharge at 0.5C to 2.5 V, then charge at 3C to 3.65 V again, charge at a constant voltage of 3.65 V until the current decreases to 0.05C, and discharge at 0.5C to 2.5 V. Each cycle at a single rate point is counted 10 times, and only the last charge is performed to the full charge state. For lithium plating at different rates, only the charge and discharge rate magnitudes are changed. (Note: The criteria for judging lithium plating. Slight lithium plating usually shows only a small amount of metallic lithium deposition on the negative electrode surface, and lithium plating occurs at the creases and corners; lithium plating means that about 50% of the negative electrode sheet surface shows lithium plating; severe lithium plating means there is a large amount of metallic lithium deposition on the negative electrode surface, even forming lithium dendrites.)

[0135] The test results of the peel strength and film resistance of the negative electrode sheets prepared in each example and comparative example are shown in Table 1.

[0136] The test results of the battery capacity retention rate of the batteries further prepared from the negative electrode sheets prepared in each example and comparative example are shown in Table 2.

[0137] The test results of the lithium plating of the batteries further prepared from the negative electrode sheets prepared in each example and comparative example are shown in Table 3.

[0138] Table 1

[0139] Peeling force / N Diaphragm resistance / mohm Example 1 0.31 1.05 Example 2 0.29 1.04 Example 3 0.29 1.12 Example 4 0.32 1.02 Example 5 0.29 1.13 Comparative Example 1 0.21 1.16 Comparative Example 2 0.16 1.17 Comparative Example 3 0.22 1.15

[0140] It can be seen from Table 1 that Examples 1 to 3 with surface coatings have higher peel strengths, and the peel strength of the multi-layer structured electrode sheets in the comparative examples is higher than that of the single-layer electrode sheets, indicating that the secondary battery electrode sheet structure designed in the present invention has excellent peel strength, which guarantees the basis for the excellent performance of the battery. The film resistances of each group are all relatively low and the differences are small, but the film resistances of Comparative Examples 1 to 2 without surface coatings increase slightly, indicating that the secondary battery electrode sheet structure designed in the present invention has good electrical conductivity.

[0141] Table 2

[0142]

[0143]

[0144] Table 3

[0145] 3C 4C 5C Example 1 No lithium deposition No lithium deposition Slight lithium deposition Example 2 No lithium deposition No lithium deposition Slight lithium deposition Example 3 No lithium deposition No lithium deposition Slight lithium deposition Example 4 No lithium deposition No lithium deposition Slight lithium deposition Example 5 No lithium deposition No lithium deposition Slight lithium deposition Comparative Example 1 No lithium deposition Slight lithium deposition Lithium deposition Comparative Example 2 No lithium deposition Lithium deposition Severe lithium deposition Comparative Example 3 No lithium deposition Slight lithium deposition Lithium deposition

[0146] As can be seen from Table 2 and Table 3, the capacity retention rates of Examples 1 to 3 at 3C are all higher than those of the comparative examples, and the capacity retention rate of Comparative Example 1 is higher than that of Comparative Example 2, indicating that the negative electrode sheets of the multi-layer material can improve the rate performance of the battery. The design of the secondary battery electrode sheet of the present invention enables the battery to have a better cycle trend and a longer cycle life due to the optimized fast charging ability during normal temperature fast charging cycling. In addition, the surface coating can effectively alleviate the problem of lithium dendrite growth during the deposition / dissolution process of lithium metal, and the lithium battery containing the negative electrode sheet with the multi-layer structure exhibits high energy density and safety. In summary, the secondary battery electrode sheet of the present invention is beneficial to improving the comprehensive performance of the battery.

[0147] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a negative electrode current collector, a first negative electrode active layer disposed on at least one side of the negative electrode current collector in a thickness direction, a second negative electrode active layer disposed on the first negative electrode active layer and away from the negative electrode current collector, and a first functional layer disposed on the second negative electrode active layer and away from the first negative electrode active layer, wherein the first functional layer contains lithium titanate; The first functional layer includes at least three regions arranged in sequence along a first direction, and the surface density of each region decreases in sequence along the first direction, and the difference in surface density between any two adjacent regions is 20-80%; the first direction is the direction from the pole ear side to the direction away from the pole ear side in the width direction of the negative electrode sheet.

2. The negative electrode sheet according to claim 1, characterized in that: The first functional layer includes a first region, a second region and a third region sequentially arranged along a first direction; The surface density of the first region is 0.008-0.0126 g / 1540.25 mm 2 ; The surface density of the second region is 0.0045-0.007 g / 1540.25 mm 2 ; The surface density of the third region is 0.0025-0.0039 g / 1540.25 mm 2 .

3. The negative electrode sheet according to claim 1, characterized in that: The surface density of the first negative electrode active layer is 0.0715-0.0775 g / 1540.25 mm 2 The surface density of the second negative electrode active layer is 0.0725-0.0825 g / 1540.25 mm 2 .

4. The negative electrode sheet according to claim 1, characterized in that: The porosity of the first negative electrode active layer is less than the porosity of the second negative electrode active layer, and the difference between the porosity of the first negative electrode active layer and the porosity of the second negative electrode active layer is 10-20%; Optionally, the porosity of the first negative electrode active layer is 20-25%; the porosity of the second negative electrode active layer is 25-40%; Optionally, in the first functional layer, the porosity of the first region is 30-34%, the porosity of the second region is 36-41%, and the porosity of the third region is 42-50%.

5. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The ratio of the thickness of the first negative electrode active layer to the thickness of the second negative electrode active layer is 1:(1.2-1.5); The ratio of the thickness of the first negative electrode active layer to the thickness of the first functional layer is 1:(0.02-0.25); Preferably, the thickness of the first negative electrode active layer is 40-100 μm; The thickness of the second negative electrode active layer is 48-150 μm; The thickness of the first functional layer is 2-10 μm.

6. The negative electrode sheet according to claim 1, characterized in that: The first negative electrode active layer comprises a first negative electrode material, and the second negative electrode active layer comprises a second negative electrode material; The ratio of Dv50 of the first negative electrode material to Dv50 of the second negative electrode material is 1:(0.55-1.14).

7. The negative electrode sheet according to claim 6, characterized in that: The Dv50 of the first negative electrode material is 7.5-10 μm; and / or, The Dv50 of the second negative electrode material is 5.5-8.5 μm; and / or, The Dv50 of the lithium titanate is 0.4-3 μm.

8. The negative electrode sheet according to claim 7, characterized in that: The first negative electrode material and the second negative electrode material are each independently selected from at least one of graphite, hard carbon, silicon oxygen and silicon carbon; Preferably, the first negative electrode material is graphite, and the second negative electrode material is graphite; More preferably, the first negative electrode material is primary particles of graphite, and the second negative electrode material is secondary particles of graphite.

9. The negative electrode sheet according to claim 7, characterized in that: The content of lithium titanate in the first functional layer is 92-96 wt %; and / or, In the first negative electrode active layer, the content of the first negative electrode material is 90-99 wt %; and / or, In the second negative electrode active layer, the content of the second negative electrode material is 80-98 wt %.

10. A battery, characterized in that: The battery comprises the negative electrode sheet according to any one of claims 1 to 9.